SPORTS VIDEOGAMES. A RETROSPECTIVE ANALYSIS IN SPAIN (1980-2015) - Marín Montín, Joaquín (Revista Conhecimento Online: Diversidade e Inclusão Social, 2016)
This text is part of a broader study whose main objective is to establish an overview about sports videogames in the Spanish context, examining their origin, history and evolution until the current moment. It examines a variety of the most representative sports games created in Spain by different companies since the late 1980s until 2015. The data sample comes from a selection of 10 games, corresponding to the most representative Spanish video game developers. Based on the results obtained we will contribute to the emerging field of sports videogames academic research with this specific analysis of phenomenon in Spain.